Analysis of Coconut (Cocos Nucifera L) Commodities Based on Land Suitability in the Pining District of Gayo Lues - Lindawati, Lindawati; Alfiansyah, Ikhwan; Madiyoh, Abdulhakim (JURNAL GEOGRAFI, 2023)
Using a survey method, this study aimed to examine the characteristics of the land and the direction of land usage for cultivating coconuts. The land's features are described in a land map created from the overlapping findings of each land map unit, which serves as a foundation for additional study to fit the environment for growing coconut plants. According to the results of the analytics and planning of the land conservation of coconut crops in Gayo Luwes, for the crops to survive, it is vital to pay attention to soil characteristics such as temperature, rainfall, soil type, and the number of wet months. Gayo Luwes District is a coconut region in the centre of the country. Not only were the results of matching for the coconut commodity in each SST obtained by using map-based planning geographic information systems, but it was also discovered that rainfall ranged from 3100 mm/year, temperatures went from 23oC to 24oC, base saturation was in the very low to low category (3.91% -35.16%), pH H2O is classified as acidic (4.6-4.9), drainage is slightly obstructed, relatively fast and good, slopes are sloping to steep (12%-26 ) and textures with values little fine, smooth and rather rough are the limiting factors dominant. Other findings also suggest that applying organic material in garbage and compost to Red Yellow Podzolic soil in Batanghari, Jambi, increases Ca-dd and base saturation, and liming is done to raise the pH of H2O in soil units. Moderate to high levels of management can improve the slope limiting factor, such as delaying erosion, establishing a terrace, planting according to the contour, and growing covering plants. Irrigation and irrigation systems can assist in increasing the factors that limit rainfall. Keywords: Development, Coconut, Land Suitability, Gayo Lues